Determination of the effect of Morus alba cv. Cubana on the population of methanogens within the rumen liquor of water buffaloes, using the Denaturing Gradient Gel Electrophoresis (DGGE). Technical note - González, Niurca; Galindo, Juana; Navarrete, A. Aparecido; Abdalla, Adibe Luiz; Mui Tsai, Siu (Cuban Journal of Agricultural Science, 2016)
The effect of mulberry (Morus alba cv. Cubana) on the population of methanogens within the rumen liquor of water buffaloes was determined using the Denaturing Gradient Gel Electrophoresis (DGGE). For this, an in vitro fermentation was made and five treatments were evaluated, which corresponded to different inclusion levels of mulberry into the diet based on star grass (SG) (Cynodon nlemfuensis): (1) 100 % of SG (control); (2) SG + 15 % M. alba cv. Cubana; (3) SG + 20 % M. alba cv. Cubana; (4) SG + 25 % M. alba cv. Cubana and (5) SG + 30 % M. alba cv. Cubana. Before the analysis of samples, a standardization of the DGGE was carried out. After 12 h of fermentation, samples of the rumen liquor were taken, from which the DNA was extracted and the DGGE was performed. The gel was scanned, images were analyzed by the Bionumerics software and dendrograms of similarities were performed. As a result, the levels of inclusion of M. alba cv. Cubana did not produced marked variations in the composition of ruminant methanogens regarding the control, grouping all treatments in a cluster with 81 % of similarity. It can be concluded that M. alba cv. Cubana has no marked effect on the population of methanogens within rumen liquor of water buffaloes. Key words: mulberry, methanogenic Archaea, DGGE, rumen, water buffaloes